Faktor-Faktor yang Mempengaruhi Minat dan Penjualan Kartu Kredit BCA di PT. DIKA - Andrie Alexcandra Kusumahdinata; Levyda Levyda; Fauziah Eddyono (Penerbit Goodwood, 2025)
Purpose: The purpose of the thesis is to analyze the impact of the COVID-19 pandemic on credit card sales performance at PT Danamas Insan Kreasi Andalan (PT DIKA), with a focus on factors influencing customer behavior in credit card usage. It uses statistical methods to evaluate changes before and after the pandemic.Methodology/approach: The methodology in this study adopts a descriptive and quantitative approach, utilizing hypothesis testing. The data consists of both primary and secondary sources, with samples drawn from PT Danamas Insan Kreasi Andalan (PT DIKA) customers, specifically credit card holders.Results/findings: The research finds that consumer demand for credit cards decreased during the pandemic due to changes in financial behavior and income instability. However, income, credit limits, down payments, and low-interest rates continue to attract consumers. Credit cards remain relevant, especially for consumers with stable jobs and income.Conslusions: Factors such as income, limit, down payment and low interest are still the main attractions for consumers in deciding to have a credit card.Limitations: The limitations of the research include data constraints from the year 2023, and a reliance on surveys from active credit card users. Additionally, easier access to credit cards raises concerns about promoting a consumerist lifestyle that can lead to higher financial burdens.Contribution: This study provides an analysis using an econometric model based on a survey of users and non-users of credit cards for a specific corporation engaged in the credit card business. Additionally, the results offer a practical overview for further analysis in terms of financial and managerial aspects. Keywords: Banking Services, Credit Card, Economic Impact, Income Stability, SalesHow to Cite: Dinata, A, A, K., Levyda., Eddyono. (2025). Faktor-Faktor Yang Mempengaruhi Minat Untuk Memiliki Kartu Kredit Performance Hasil Penjualan Sales Kartu Kredit BCA di PT Danamas Insan Kreasi Andalan (PT DIKA). Studi Ilmu Manajemen dan Organisasi, 6(1), 1-20.